2015
DOI: 10.1007/s00396-015-3637-1
|View full text |Cite
|
Sign up to set email alerts
|

Reactive poly(ethylene-co-vinyl alcohol) monoliths with tunable pore morphology for enzyme immobilization

Abstract: Poly(ethylene-co-vinyl alcohol) (EVOH) monoliths were fabricated from two kinds of EVOH with different ethylene contents by thermally induced phase separation (TIPS) technique using a mixed solvent of isopropanol (IPA) and water. The pore and skeleton sizes could be controlled by changing the fabrication parameters such as the concentration of the polymer, the ratio of IPA and water, and the cooling temperature. The EVOH monoliths possessed relatively high specific surface area and uniform mesopore structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Before enzyme immobilization, the hydroxyl groups of the EVOH monolith were activated with CDI in anhydrous ACN solution. The activated EVOH monolith contained imidazolyl carbamate groups which could react with free amino groups in the enzyme . Catalase was immobilized on the activated hydrophilic EVOH monolith.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before enzyme immobilization, the hydroxyl groups of the EVOH monolith were activated with CDI in anhydrous ACN solution. The activated EVOH monolith contained imidazolyl carbamate groups which could react with free amino groups in the enzyme . Catalase was immobilized on the activated hydrophilic EVOH monolith.…”
Section: Resultsmentioning
confidence: 99%
“…Because of its hydrophilicity, biocompatibility, thermal stability, and chemical resistance, EVOH has great potential to be used as a unique biomedical material . Recently, we have fabricated an EVOH‐based monolith by using TIPS technique for the first time . The EVOH monolith possessing hydrophilic hydroxyl groups has many superior properties over other hydrophobic polymers for enzyme immobilization …”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Our research group reported that a solution of poly(methyl methacrylate) (PMMA) and its copolymer with glycidyl methacrylate-which was dissolved in a mixture of heated ethanol and water-formed a solid white monolith after cooling and drying. [24,25] In addition, monoliths of a series of other polymers such as polyacrylonitrile copolymer, [26] poly(γ-glutamic acid), [27] poly(ethylene-co-vinyl alcohol), [28] poly(l-lactic acid), [29] and cellulose acetate (CA) [30] have been developed using the TIPS method.…”
Section: Introductionmentioning
confidence: 99%
“…We have achieved facile fabrication of porous monoliths from polymer solutions using thermally induced phase separation (TIPS). Monoliths of PMMA, poly­(acrylonitrile), poly­(vinyl alcohol), poly­(ethylene- co -vinyl alcohol), and poly­(γ-glutamic acid) were successfully prepared by selecting an appropriate mixed solvent. Additionally, organic–inorganic hybrid monoliths were also prepared by TIPS, which were applied for battery materials, adsorbents, separation media, and catalyst carriers. …”
Section: Introductionmentioning
confidence: 99%